Heterotrophic bacterial responses to the winter–spring phytoplankton bloom in open waters of the NW Mediterranean. (February 2015) - Gomes, Ana; Gasol, Josep M.; Estrada, Marta; Franco-Vidal, Leticia; Díaz-Pérez, Laura; Ferrera, Isabel; Morán, Xosé Anxelu G.
Abstract: The response of planktonic heterotrophic prokaryotes to the NW Mediterranean winter–spring offshore phytoplankton bloom was assessed in 3 cruises conducted in March, April–May and September 2009. Bulk measurements of phytoplankton and bacterioplankton biomass and production were complemented with an insight into bacterial physiological structure by single-cell analysis of nucleic acid content [low (LNA) vs. high (HNA)] and membrane integrity ("Live" vs. "Dead" cells). Bacterial production empirical conversion factors (0.82±0.25 SE kg C mol leucine −1 ) were almost always well below the theoretical value. Major differences in most microbial variables were found among the 3 periods, which varied from extremely high phytoplankton biomass and production during the bloom in March (>1 g C m −2  d −1 primary production) to typically oligotrophic conditions during September stratification (<200 mg C m −2  d −1 ). In both these periods bacterial production was ~30 mg C m −2  d −1 while very large bacterial production (mean 228, with some stations exceeding 500 mg C m −2  d −1 ) but low biomass was observed during the April–May post-bloom phase. The contribution of HNA (30–67%) and "Live" cells (47–97%) were temporally opposite in the study periods, with maxima in March and September, respectively. Different relationships were found between physiological structure and bottom-up variables, with HNA bacteria apparently more responsive to phytoplankton only during the bloom, coinciding with larger average cell sizes of LNA bacteria. Moderate phytoplankton–bacterioplankton coupling of biomass and activity was only observed in the bloom and post-bloom phases, while relationships between both compartments were not significant under stratification. With all data pooled, bacteria were only weakly bottom-up controlled. Our analyses show that the biomass and production of planktonic algae and bacteria followed opposite paths in the transition from bloom to oligotrophic conditions. Highlights: Heterotrophic prokaryotes and phytoplankton were studied in the open NW Mediterranean. Primary production and bacterial production peaks were lagged by ca. 1.5 months. Bacterial single-cell properties correlated better with phytoplankton than bulk data. Bacteria were bottom-up controlled by algal DOM only in the bloom and post-bloom.